2015
DOI: 10.1111/lasr.12166
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Amicus Curiae Briefs on U.S. Supreme Court Opinion Content

Abstract: We address fundamental questions about the ability of interest groups to shape public policy by examining the influence of amicus curiae briefs on U.S. Supreme Court majority opinion content. We argue that the justices will incorporate language from amicus briefs into their opinions based on the extent to which the amicus briefs contribute to their ability to make effective law and policy. Using plagiarism detection software and other forms of computer assisted content analysis, we find that the justices adopt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
38
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(40 citation statements)
references
References 48 publications
2
38
0
Order By: Relevance
“…To assess the complexity of different regulatory consultations and differentiate between relatively straightforward proposed regulations from ones that are less clear, we made use of a dictionary‐based program called Linguistic Inquiry and Word Count (LIWC) already used in extent literature assessing interest group lobbying dynamics in legal settings (Owens & Wedeking ; Collins et al . forthcoming) to generate a score of cognitive complexity for each regulation in our data…”
Section: Section 4: Regression Analysismentioning
confidence: 99%
“…To assess the complexity of different regulatory consultations and differentiate between relatively straightforward proposed regulations from ones that are less clear, we made use of a dictionary‐based program called Linguistic Inquiry and Word Count (LIWC) already used in extent literature assessing interest group lobbying dynamics in legal settings (Owens & Wedeking ; Collins et al . forthcoming) to generate a score of cognitive complexity for each regulation in our data…”
Section: Section 4: Regression Analysismentioning
confidence: 99%
“…Earlier research shows that Supreme Court justices rely so heavily on information in amicus briefs, that they often signal their need for these documents to interest groups (Hansford and Johnson ). Moreover, previous works have found that amicus briefs do not just influence the justices' final decisions on the merits of a case (Box‐Steffensmeier et al ; Collins et al ), they also affect the justices' decision to hear a case in the first place, namely to “grant certiorari” to a legal case coming from a lower court (Caldeira and Wright ; Owens and Black ). In addition, other studies suggest that amicus briefs may have a significant effect on the likelihood of dissenting opinions (Collins ).…”
mentioning
confidence: 99%
“…Prior work suggests that the justices are asymmetrically influenced by their clerks (see Kromphardt, 2015, 2017; Ward and Weiden, 2006). Existing research also demonstrates differences in how much language the justices adopt from party and amicus curiae briefs (Corley, 2008; Collins, Corley, and Hamner, 2015) as well as lower court opinions (Corley, Collins, and Calvin, 2011). The differences among justices in some instances can be substantial.…”
Section: The Varying Tendencies Of Supreme Court Justicesmentioning
confidence: 99%